Crescimento e desenvolvimento de angiquinho (Aeschynomene spp.) - Moraes, Caroline Leivas (2007)
Weeds interfered negatively on development and crop productivity of rice (Oryza sativa L.). In order to determine growth and development, reproductive capacity of angiquinho (Aeschynomene spp.) weeds, the physiological quality of seeds, morphological characteristics and dry matter partition among organs were conducted several assays. The germination percentage and first account were of 89% at eighth day of germination, and of 74% at fifth day after sowed, respectively. The germination speed index was 17,6 at eighth day, while emergence percentage and emergence speed index were of 83% and 3,2, respectively. The maximum crop growth rate was 41,15 g m-2 d-1 attained on 49 days after emergence (DAE). The maximum leaf area index was 3,43 m2 m-2 obtained on 56 DAE. The relative growth rate, leaf area ratio and leaf mass ratio decreased with plant ontogeny. On the other hand, the assimilatory leaf rate increased gradually until the 49 DAE with x value of 16,12 g m-2 d-1, showing a second pick on 70 DAE with value of 15,4 g m-2 d-1, and finally decreasing accenttuality after 73 DAE. The partition of fotoassimilates was sequential among organs. Initially, the preferential metabolic sinks were leaves, roots and stems and aposteriori with appearance of legumes these became preferential metabolic sink of definitive and irreversible, provoking a reduction on accumulate of dry matter of leaves after 56 DAE, stems next 77 DAE and roots behind 84 DAE, but always with positive values until the final hawest.